Penerapan Syllable Method sebagai Upaya Mengatasi Literasi Dasar pada Warga Belajar Program Kesetaraan Kelas Inklusi Paket B SKB Gudo Jombang - Erlinia, Sintia Dwi; Nusantara, Widya (J+PLUS UNESA, 2024)
The fridayApplication of the syllable method, which is a lesson that has been implemented since 2019 in the National Junior High School Equivalency Gudo Jombang Package B Inclusion Class Equality Program. The application of this method is an effort to overcome basic literacy in learning residents. The aim of this research is to describe and determine the supporting and inhibiting factors for Syllable Method learning as an effort to overcome basic literacy in the National Junior High School Equivalency Gudo Jombang Package B Inclusion Class Equality Program. The method used is descriptive qualitative, through data collection techniques of participatory observation, in-depth interviews, and documentation. This research uses data analysis in the form of data collection, data reduction, data presentation, and conclusions. The results of the research show that the syllable method learning planning is carried out in an educational and effective manner. There are 5 basic literacies which are applied in reading and writing, numeracy, science, digital and financial literacy. There are supporting and inhibiting factors in implementing the syllable method of learning. The supporting factor is supporting infrastructure. There is interest among students in the basic literacy learning process, while the inhibiting factor is that there are students whose learning process is slow so they need intensive guidance to